BIBLIOKONSELING VIRTUAL: METODE PENGURANGAN TINDAK PIKIRAN PORNOGRAFI PADA SISWA SMPN 1 KARANGPLOSO - Laili Azkiyah (Center of Language and Cultural Studies, 2017)
This classroom action research explores the use of virtual biblicouncelling to reduce the acts on pornography abuses to SMPN 1 Karangploso Malang. This study was implemented in two cycles each of which was defined in four steps: planning, acting, observing, and reflection. The results showed that the implications of changes in the status of the superego is more robust to reduce acts of pornography. Students are gradually able to control the acts of pornographic thoughts including: imagery porn actions and matters that deal with pornographic actions, pornographic images or videos or to do so with the guidance of the group and virtual bibliocouncelling approach.